Identification of causes and consequences of Kolberi among Iranian Kurdish women: a grounded theory study - Javad Yoosefi Lebni; Seyed Fahim Irandoost; Arash Ziapour; Ahmad Ahmadi; Nafiul Mehedi; Seyyed Amar Azizi (BMC Women's Health, 2023)
Abstract Background Women turn to Kolberi for various reasons, which cause numerous challenges for them. Thus, it is imperative to identify these causes and problems. Since no study has ever been undertaken to deal with this participant, the present research aims to identify the causes and consequences of Kolberi among Kurdish women in Iran. Method The present research uses the grounded theory approach to investigate 28 female Kurdish Kolbers. To achieve several participants, purposive, snowball, and theoretical sampling methods were used, while face-to-face semi-structured interviews were used to gather data. The process of data collection and analysis took 10 months, from April to December 2022. The data were analyzed using the Strauss and Corbin method and MAXQDA-20018 software. The Guba and Lincoln criteria were also met to increase the trustworthiness of the results. Findings Analysis of the data led to 143 initial codes, 31 subcategories, and 9 main categories: Causal condition (individual characteristics and economic factors); predisposing conditions (social and cultural factors, familial factors); intervening conditions (advantages and characteristics of Kolberi); strategies (strengthening compatibility with Kolberi); and consequences (individual problems, social problems and positive consequences). Conclusion Measures such as training occupational skills for women and providing employment conditions for them, increasing social, financial, and mental support for women without guardians, creating border markets, and expanding women's handicrafts can help prevent female Kolberi.